Analisis Kesulitan Belajar Siswa Dalam Proses Pembelajaran Komputer dan Jaringan Dasar Pada Kelas XI SMKN 1 Ranah Ampek Hulu Tapan - Zari, Dhantik Fermata; Alfiriani, Adlia; Nurdin, Bernediv (Journal of Computer Science and Information System(JCoInS), 2023)
This research aims to determine the level of student learning difficulties in learning computers and basic networks in class Xl at SMKN 1 Ranah Ampek Hulu Tapan for the 2023/2024 academic year. This research is descriptive using a quantitative approach using a questionnaire. The population in this study was class Xl students at SMKN 1 Ranah Ampek Hulu Tapan using a saturated sampling technique. The results of this research show that the learning difficulties of class, 5) Family skills at 72%, 6) Community skills at 75%. The results showed that class Xl students at SMKN 1 Ranah Ampek Hulu Tapan. The 2023/2024 school year has a level of student learning difficulty in the "Good" category, with the lowest percentage of family skills getting a score of 72%, while the highest percentage of school skills gets a score of 87%. Based on the ANOVA output, it is known that the significance value (sig) is 0.743 > 0.05, so it can be concluded that the average learning difficulty of students from each occupational group of farmers, traders and entrepreneurs is "SAME" in significance.